Cold vengeance - Preston, Douglas J. (Preston, Douglas J. Pendergast novel., 2011)
"A bonding trip for Pendergast and his brother-in-law, Judson Esterhazy, turns violent. Before abandoning a mortally-wounded Pendergast, Esterhazy announces his sister, Pendergast's long-dead wife Helen, is alive"--Provided by publisher.